Improving the quality of pigskin leather texture images using enhanced image processing - Mohd Hafrizal Azmi, Fakhrul Zaman Rokhani, Raja Syamsul Azmir Raja Abdullah; M. Iqbal Saripan (African Journal of Pig Farming, 2019)
In this paper, we propose a method to improve the quality of pigskin leather texture images using digital image processing approach. The proposed method intends to minimize the imbalance illumination problem that occurs in the images captured from consumer leather products. This method is compared with the other methods in the literature such as contrast adaptive binarization method, and the results showed that the proposed method yielded better results in terms of highlighting the special characteristics of pigskin in consumer leather products.